MACROECONOMIC OUTLOOK THROUGH THE EYES OF INVESTORS: FINANCIAL INSTRUMENTS AND FAIR VALUE MEASUREMENT - Olivera Ecaterina OROS (Challenges of the Knowledge Society)
A country's economy growth is depending on the investments, either direct or indirect, made in it. Also, the level of the foreign direct investments is a relevant indicator for other potential investors. While lenders are looking at the financial statement to understand the company's ability to repay debt, the investors are looking at the financial statements to understand the company's ability to grow. The IASB's Conceptual framework for financial reporting offers a standardized model of financial statement that is about to change.